SEDENTARY LIFESTYLE SEBAGAI FAKTOR RISIKO TERHADAP KEJADIAN OBESITAS ANAK STUNTED USIA 9-12 TAHUN DI KOTA SEMARANG - Puspasari, Indah; Sulchan, Muhammad; Widyastuti, Nurmasari (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2017)
Introduction: Sedentary lifestyle is associated with minimum physical activity with energy expenditure equivalent to 1-1.5 metabolic equivalents (METs). Sedentary lifestyle can lead to the increasing energy storage as fat deposit and eventually can cause obesity. This study aimed to determine sedentary lifestyle as a risk factor stunted children on obesity in Semarang.Methods: This study used a cross-sectional design with two groups, height below the median-obesity (TBBM-O) and height below the median-non obesity (TBBM-NO). Screening was done in 602 children aged 9-12 years in urban and suburban areas in Semarang. Measurement of sedentary lifestyle using Physical Activity Questionnaire for Children (PAQ-C). Sedentary lifestyle was high if score â‰¥ 3 and low < 3. Prevalence ratio was obtained by using Chi-Square analysis.Results: The prevalence of stunted was 9.4% and stunted obesity was 0.2%. The sedentary lifestyle score on TBBM-O was higher (95%) than TBBM-NO (80%) with prevalence ratio = 4.750 (CI = 0.481-46.906) and (p = 0.151).Conclusion: Children with a high sedentary lifestyle had 4.7 times higher risk to obesity than low sedentary lifestyle.